The law of the canals and postural clinic* - Gagey, Pierre-Marie (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
An hypothesis on the construction of the coherence of the perception of space, visual and proprioceptive, through the three afferents, retinal, oculomotor and canalicular, allows us to offer a way to deconstruct this consistency by an optical prism. And this deconstruction exhibits the organization between space perception and regulation of the postural tonic activity.